Water microbial quality of lima’s beaches and its relation with the pollution causes - Vergaray U., Germán (2011)
acceptable, then detect the pollution source. It was performed a microbiologicalanalysis of the water of 21 Lima’s beaches and the detections of contamination sources with human feces. The results qualify the water of 33.33% (07) beaches as unacceptable if it is used as indicators of fecal pollution, the total coliforms and fecal coliforms; if it is included Escherichia coli, it reaches to 47.62% (10); and if also it is included Enterococcus it reaches to 66.66%(14). It was demonstrated the existence of domestic sewage discharge in all the beaches considered as unacceptable; in 35.75% (05) with visual inspection; in 14.29% (02) was observed water running with fecal pollution and in 50% (07) by the relation between E. coli and Enterococcus.